The Influence Of Cash Ratio, Current Ratio, and Debt To Total Asset On Cash Dividend in Large Compsumption and Production Goods Trading Sector Companies Listed on The Indonesian Stock Exchange In The Financial Reporting Period 2013 to 2018 - Yanuardi Sadewa (Journal of Entrepreneur and Business, 2024)
This study aims to analyze the effect of Cash Ratio, Current Ratio, and Debt to Total Assets (DTA) on Cash Dividends in large consumer goods and production trade companies listed on the Indonesia Stock Exchange in the 2013 to 2018 financial reporting period. This research is an explanatory research explain the causality relationship using secondary data with the population is that all sectors of the wholesale trade of consumer goods and production listed on the IDX in 2018 are 35 companies. A sample of 7 companies was selected using the purposive sample method in accordance with predetermined criteria including being listed on the IDX and delivering in full accordance with the required information, namely Cash Dividends, Cash Ratio, Current Ratio, and Debt to Total Assets (DTA) during period 2013 - 2018. The method of analysis used is linear regression panel data. The results showed that at the 95% confidence level of the three dependent variables studied, namely: Cash Ratio, Current Ratio, and Debt to Total Assets (DTA), there is one variable that has a significant effect on Cash Dividend of companies in the wholesale trade sector of consumer goods and production, namely Cash ratio. Meanwhile, if tested simultaneously, the Cash Ratio, Current Ratio, and Debt to Total Assets (DTA) have a significant effect on Cash Dividends. Keywords: Cash Ratio, Current Ratio, and Debt to Total Assets (DTA) and Cash Dividends